Development Of A Rapid Molecular-Based Diagnostic Kit For Diagnosis Of Leptospirosis - Somkuna, Narumon (2004)

(untitled)
Leptospirosis is a worldwide zoonosis, affecting farm animals, wildlife as well as humans particularly in tropical areas. It is a re-emerging infectious disease caused by pathogenic leptospires. Diagnosis of leptospirosis usually depends upon demonstration of serum antibodies by serological tests. These tests are relatively not specific, sensitive and often time-consuming. Early, quick and precise diagnosis is essential so that early and specific treatment of patients can be provided and also allows for suitable control of infection to be implemented. The primary objective of this study to use a polymerase chain reaction (PCR) assay as a major technique to detect and differentiate pathogenic leptospires. In addition, another aim of this study was to develop a diagnostic kit based on PCR assay coupled with DNA hybridization assay. The assay used a nonradioactive leptospiral DNA probe hybridized to target leptospiral DNA in a microtitre plate for the detection of leptospiral DNA in clinical specimens. Twenty-one reference leptospiral serovars representing four species of Leptospira (L. interrogans, L. weilii, L. inadai and L. borgpetersenii) and clinical samples were examined. Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) and Low-Stringency-PCR (LS-PCR) were applied to detect and differentiate the leptospires. The results from PCR-RFLP showed that restriction enzymes: DdeI, NdeII, and MspI could digest the amplified leptospiral DNA with genus specific primers G1/G2 and allowed differentiation of the leptospiral serovars and serogroups into their species level. It is seen that LS-PCR could produce serovar specific DNA fingerprintings. Nonradioactive digoxigenin (DIG)-labelled leptospiral DNA probes and dot blot hybridization (DBH) assay were successfully developed for the detection of leptospiral DNA in cultures and clinical samples. Results showed that these probes had a high sensitivity and specificity. The lowest limit of the DNA concentration in PCR-DBH assay was 10-6 μg. A new and rapid diagnostic kit was thus designed. This PCR-MHA detection method has advantages over the conventional PCR assay and DBH assay when handling a large number of samples. The procedure has fewer steps and it is fast, safe and easy to handle. Results showed it has high specificity, sensitivity and reproducibility. Furthermore, the assay could be used to detect leptospiral DNA using reagents and standard laboratory ELISA equipment. Moreover, the entire method could be completed within a day. The technique could be directly applied to clinical samples such as urine and serum for rapid diagnosis of leptospirosis. The technique used in this study will be useful for detection and identification of leptospirosis in patients. Moreover, it could also be used on farm animals for screening and detection of uninfected animals.